Plasmonic spectrum on 1D and 2D periodic arrays of rod-shape metal nanoparticle pairs with different core patterns for biosensor and solar cell applications. (7th October 2016) - Kumara, N T R N; Chau, Yuan-Fong Chou; Huang, Jin-Wei; Huang, Hung Ji; Lin, Chun-Ting; Chiang, Hai-Pang
Abstract: Simulations of surface plasmon resonance (SPR) on the near field intensity and absorption spectra of one-dimensional (1D) and two-dimensional (2D) periodic arrays of rod-shape metal nanoparticle (MNP) pairs using the finite element method (FEM) and taking into account the different core patterns for biosensor and solar cell applications are investigated. A tunable optical spectrum corresponding to the transverse SPR modes is observed. The peak resonance wavelength ( λ res ) can be shifted to red as the core patterns in rod-shape MNPs have been changed. We find that the 2D periodic array of core–shell MNP pairs (case 2) exhibit a red shifted SPR that can be tuned the gap enhancement and absorption efficiency simultaneously over an extended wavelength range. The tunable optical performances give us a qualitative idea of the geometrical properties of the periodic array of rod-shape MNP pairs on SPRs that can be as a promising candidate for plasmonic biosensor and solar cell applications.